2019
DOI: 10.1017/s1041610219000644
|View full text |Cite
|
Sign up to set email alerts
|

Verbal fluency as a screening tool for mild cognitive impairment

Abstract: Objectives: The goal of this study was to evaluate the ability of semantic (animal naming) and phonemic (FAS) fluency in their ability to discriminate between normal aging, amnestic-Mild Cognitive Impairment (a-MCI), and Alzheimer’s disease (AD). Design: We used binary logistic regressions, multinomial regressions, and discriminant analysis to evaluate the predictive value of semantic and phonemic fluency in regards to specific diagnostic classifications. Setting: Outpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 35 publications
0
36
0
2
Order By: Relevance
“…Afterward, the participants were assessed using the following neuropsychological tests, covering three cognitive domains: (1) episodic memory assessed by Auditory–Verbal Learning Test–Huashan version (AVLT-H) ( Zhao et al, 2012 ), using the delayed recall and delayed recognition scores; (2) speed/executive function assessed by trail-making test (TMT) parts A and B ( Perrochon and Kemoun, 2014 ), using the time spent for completing TMT A and TMT B; and (3) language function assessed by verbal fluency ( McDonnell et al, 2020 ) and Boston Naming Test ( Stålhammar et al, 2016 ), using the scores of both tests. Meanwhile, depression level was assessed using the 30-item Geriatric Depression Scale (GDS-30) ( Chau et al, 2006 ).…”
Section: Methodsmentioning
confidence: 99%
“…Afterward, the participants were assessed using the following neuropsychological tests, covering three cognitive domains: (1) episodic memory assessed by Auditory–Verbal Learning Test–Huashan version (AVLT-H) ( Zhao et al, 2012 ), using the delayed recall and delayed recognition scores; (2) speed/executive function assessed by trail-making test (TMT) parts A and B ( Perrochon and Kemoun, 2014 ), using the time spent for completing TMT A and TMT B; and (3) language function assessed by verbal fluency ( McDonnell et al, 2020 ) and Boston Naming Test ( Stålhammar et al, 2016 ), using the scores of both tests. Meanwhile, depression level was assessed using the 30-item Geriatric Depression Scale (GDS-30) ( Chau et al, 2006 ).…”
Section: Methodsmentioning
confidence: 99%
“…Further, this association was not mediated by cognitive reserve in the younger adults but was mediated by cognitive reserve in the older adults, thus, presumably representing compensation in the elderly. Our findings are relevant as verbal fluency is significantly impaired in several dementia types including Alzheimer's disease (Henry et al, 2004 ), shows early changes in mild cognitive impairment (Murphy et al, 2006 ), is sensitive to subjective cognitive decline (Nikolai et al, 2018 ), and is even suggested as a potential screening tool (McDonnell et al, 2020 ; Frankenberg et al, 2021 ). Further, subdomains of verbal fluency such as phonemic and semantic fluency evolve differentially over time, even in healthy aging (Stolwyk et al, 2015 ; Gonzalez-Burgos et al, 2019 ; Rodríguez-Aranda et al, 2020 ).…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, studies found a significant correlation between MMSE scores and Trail-Making-Test scores (particularly with TMT-B speed score: r=-0.54) in elderly subjects (Olivera-Souza et al, 2000;Saint Martin, Sforza, Barthelemy, Thomas-Anterion, & Roche, 2012). In MCI patients, studies found significant correlations between MMSE scores and TMT (with TMT-B, r=-.40), and verbal fluency (animal naming) scores (r=.38) (Jefferson et al, 2006;McDonnell et al, 2019). In a sample of the French Three-City Study (n=1.516), the total MMSE scores and episodic memory evaluated by the Free and Cued Reminding Test (FCSRT) scores were also significantly correlated (with Total score: r=.32; Free score: r=.40 and Cued score: r=.27) (Carcaillon, Amieva, Auriacombe, Helmer, & Dartigues, 2009).…”
Section: Introductionmentioning
confidence: 99%